(untitled) (UCC Law Journal, 2023)
Aside from public health devastations, one aspect of Nigeria’s national life that was severely hit by the COVID-19 pandemic, was the economic space. As part of the government’s mitigating measures, an economic stimulus package was put together to help those most hit by the crisis. However, a key item was left out i.e., legislation enacted by the Parliament, to ensure the protection of the socio-economic rights of the people. This article analyses how the Nigerian legislature could have triggered relevant provisions of the Constitution to adequately protect this class of rights, as a response to the devastating impact of the pandemic. This analysis is carried out against the backdrop of the existing non-justiciable status of socio-economic rights in the country. The article makes the point that there is a great deal of potential in the country’s constitutional framework regarding legislative powers, that could have been creatively deployed by the Parliament to enact legislation that would serve as a ’Shield’ for socio-economic rights in the pandemic, notwithstanding the clog of non-justiciability. The article concludes that the legislature as the people’s representative ought to have better executed its constitutional powers, by demonstrating uncommon courage at a time when it mattered most